Distribution of Varroatosis and Mixed Infections in Beekeeping Farms of Khorezm and Bukhara Regions - Uktamovich, Suyunov Rashid; Beknazarovich, Yunusov Khudaynazar; Buriyevich, Ibragimov Furqat; Kumushkhon, Mirzakarimova (American Journal of Bioscience and Clinical Integrity, 2025)
This article examines the epizootic situation of honey bee varroatosis in beekeeping farms of the Khorezm and Bukhara regions, assessing the prevalence (extensiveness) and intensity of infestation. Additionally, cases of mixed parasitic infections involving Varroa destructor, Tropilaelaps spp., and Nosema spp. were analyzed. The results revealed regional patterns in the distribution of varroatosis and identified the influence of climatic conditions and management practices on disease development. The study scientifically substantiates the necessity of implementing integrated pest management strategies.